Crude and refined millet bran oil alleviate lipid metabolism disorders, oxidative stress and affect the gut microbiota composition in high‐fat diet‐induced mice. (16th April 2021) - Yin, Ruiyang; Fu, Yongxia; Yousaf, Laraib; Xue, Yong; Hu, Jinrong; Hu, Xiaosong; Shen, Qun
Summary: To investigate crude millet bran oil (MBO) and refined millet bran oil (MRO) consumption on lipid metabolism in obese mice, C57BL/6 mice were fed with HFD/MBO and MRO (2 g kg −1 bw per day) for 12 weeks. Both MBO and MRO supplementation effectively alleviated hepatic lipid accumulation, which was associated with downregulation of the expression levels of acetyl‐CoA carboxylase ( Acaca ), fatty acid synthase ( Fasn ), perilipin‐2 ( Plin2 ) and stearoyl‐CoA desaturase ( Scd ). Only MBO supplementation significantly decreased plasma levels of total cholesterol (TC), catalase (CAT), hepatic lipid peroxidation and hepatic oxidative stress. It also increased the abundance of Akkermansia . The refining process caused a reduction of bioactive components (phytosterols, tocopherols and pigments) and a decrease in associated health benefits of MBO. Therefore, MBO can be moderately refined and still retain some health benefits, but new refining methods are needed to enhance the content of active compounds and improve the physiological efficacy of MRO. Abstract : The effects of crude and refined millet bran oil on lipid metabolism, oxidative stress and gut microbiota composition.